Efektifitas Perangkat Pembelajaran Pendekatan Multi Representasi Berbantuan Video Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Aris Doyan; Sutrio Sutrio; Muhammad Matori Rahman (Postgraduate, University of Mataram, 2021)
This development research aims to produce a product in the form of a video-assisted multi-representation approach learning device to improve students' critical thinking skills of sound wave concepts that are effective. The research design used is a 4D model consisting of Define, Design, Develop and Disseminate. The products developed are syllabus, Lesson Plans, Student Worksheets, Learning Videos and Critical Thinking Ability Assessment Instruments. Data collection techniques using validation sheets, critical thinking skills evaluation tool. Data on the validity and efficiency of the device were analyzed using the li scale. Product effectiveness data were analyzed using Gain standards. The average result of the N Gain test for critical thinking skills is 0.62 in the medium category, while the average N Gain test value for concept mastery is 0.73 in the high category. So, it can be concluded that the video-assisted multi-representation approach physics learning device to improve critical thinking skills in the sound wave material of students is effective